2013
DOI: 10.7314/apjcp.2013.14.1.341
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in TP53 (rs1042522), p16 (rs11515 and rs3088440) and NQO1 (rs1800566) Genes in Thai Cervical Cancer Patients with HPV 16 Infection

Abstract: The risk of cervical cancer development in women infected with HPV varies in relation to the individual host's genetic makeup. Many studies on polymorphisms as genetic factors have been aimed at analyzing associations with cervical cancer. In this study, single nucleotide polymorphisms (SNPs) in 3 genes were investigated in relation to cervical cancer progression in HPV16 infected women with lesions. Two thousand cervical specimens were typed by PCR sequencing methods for TP53 (rs1042522), p16 (rs11515 and rs3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
(43 reference statements)
1
14
3
Order By: Relevance
“…(Table IV). Accordingly, a significantly higher frequency of the CG genotype and G allele was detected in the samples in comparison with certain previous reports (20,33,35,36). Subgroup comparisons for the tumor behavior of prolactinoma have also shown that those with a high Ki67 index and with giant prolactinomas had a higher frequency of CG genotype as compared with the other groups (although not statistically significant) in the study and when compared with previous studies.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…(Table IV). Accordingly, a significantly higher frequency of the CG genotype and G allele was detected in the samples in comparison with certain previous reports (20,33,35,36). Subgroup comparisons for the tumor behavior of prolactinoma have also shown that those with a high Ki67 index and with giant prolactinomas had a higher frequency of CG genotype as compared with the other groups (although not statistically significant) in the study and when compared with previous studies.…”
Section: Discussioncontrasting
confidence: 41%
“…Furthermore, no association between haplotypes of two different single-nucleotide polymorphisms and tumor progression has been found. Chansaenroj et al (35) have indicated that the frequencies of adjacent polymorphisms are not significantly increased in abnormal cervical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In China, there are nearly 150 000 new cervical cancer patients every year, and about 20 000 women die from the disease . Although high‐risk type HPV infection is considered to be the leading cause of cervical cancer occurrence, the exact mechanism of occurrence and development of cervical cancer has not been fully elucidated . Despite the improvement of therapeutic methods and diagnostic tools, the overall prognosis of patients has not been improved .…”
Section: Introductionmentioning
confidence: 99%
“…Significant association of PP genotype of p.R72P polymorphism has been reported with increased risk for adenocarcinoma in Chinese nonsmoker females (Ren et al, 2013) and cervical cancer in Indians (Zhou et al, 2012). p.R72P polymorphism has also been reported to be associated with risk of cervical cancer development in Human papillomavirus (HPV) 16 infected women (Chansaenroj et al, 2013). In esophageal cancer, HPV may have a role only in the presence of altered promoter methylation of Aurora A and tobacco use (Mohiuddin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%